Comparison of high resolution computed tomography findings of thorax between smear negative pulmonary tuberculosis and non-pulmonary tuberculosis among patients with suspected pulmonary tuberculosis in Hospital Universiti Sains Malaysia - Chong, Yap Teck (2022)
Background: Pulmonary tuberculosis (PTB) has been around for over 100 years since it was first discovered. Despite its long existence, medical practitioners still found it challenging to diagnose sputum smear negative PTB. The ability of high resolution computed tomography (HRCT) in diagnosing PTB is still under discussion and investigation in the sputum smear-negative setting. Thus, this study was conducted to determine the HRCT findings in diagnosing early stage of active smear negative PTB and to study specific HRCT findings in diagnosing smear negative PTB. Methods: A cross-sectional study was conducted in Hospital Universiti Sains Malaysia (USM), Kota Bharu, Kelantan, Malaysia on 22 patients whose sputum smears were negative, and had undergone HRCT thorax. HRCT findings were collected and described using descriptive statistic, count (n) and percentage (%); and comparative HRCT findings between smear negative PTB versus non-PTB was analysed using the Pearson chi-square test. Results: The tree-in-bud appearance showed a significant association with smear negative PTB, with p-value of 0.046. And this main findings of tree-in-bud appearance showed significant association with smear negative PTB at S5 (medial segment) of right middle lobe and S3 (anterior segment) of left upper lobe, with p-value of 0.025 on both sides. Conclusion: Tree-in-bud appearance which indicates the early stage of active PTB, had shown significant association with smear negative PTB, and can be detected in HRCT. Hence, HRCT could be used as an alternative method to detect active PTB in the background of sputum smear-negative setting among higher risk patients.